The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12905-019-0824-0
|View full text |Cite
|
Sign up to set email alerts
|

“We are responsible for the violence, and prevention is up to us”: a qualitative study of perceived risk factors for gender-based violence among Ethiopian university students

Abstract: BackgroundThere is a high prevalence of gender-based violence (GBV) victimization among young Ethiopian women, including in universities, where female enrollment is low but growing. Understanding factors contributing to GBV in this context and students’ perspectives on gender, relationships, and interpersonal violence is essential to creating effective interventions to prevent GBV and support female students’ rights and wellbeing.MethodsIn-depth interviews (IDIs) and focus group discussions (FGDs) were held wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 20 publications
4
30
0
Order By: Relevance
“…In fact, the students say that they are very familiar with certain subtler forms of gender-based violence (e.g., situations of jealousy or feelings of possessiveness, control of the partner, sexist remarks, or psychological attack, rather than other, more open or aggressive acts (e.g., preferential treatment or academic favors in return for sexual favors, unwanted kissing and/or touching, physical assaults, or the sending of threatening or intimidating messages or emails). In this sense, other authors indicated that, on occasions, some male students expected some kind of sexual relationship if they provided support or favors to a partner, so these students justify some forms of sexual harassment [10]. These authors add that the participants tried to justify and link cases of gender-based violence within the university, indicating the inappropriate behaviors or clothing of women and the lack of personal prevention measures as possible causes of gender-based violence.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In fact, the students say that they are very familiar with certain subtler forms of gender-based violence (e.g., situations of jealousy or feelings of possessiveness, control of the partner, sexist remarks, or psychological attack, rather than other, more open or aggressive acts (e.g., preferential treatment or academic favors in return for sexual favors, unwanted kissing and/or touching, physical assaults, or the sending of threatening or intimidating messages or emails). In this sense, other authors indicated that, on occasions, some male students expected some kind of sexual relationship if they provided support or favors to a partner, so these students justify some forms of sexual harassment [10]. These authors add that the participants tried to justify and link cases of gender-based violence within the university, indicating the inappropriate behaviors or clothing of women and the lack of personal prevention measures as possible causes of gender-based violence.…”
Section: Discussionmentioning
confidence: 98%
“…In the educational environment, it should be introduced at all levels in all year groups and across the curriculum [9], so as to reduce the educational deficiencies concerning gender at the family level. In this sense, recently, several authors detect among the results of their research that gender-based violence is a phenomenon that occurs recurrently among university students [10]. Among the different typologies stands out bullying, violence and physical-sexual harassment as forms of violence; those responsible are different male members of the education community such as teachers and/or peers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the social cognitive theory to TPB, subjective norms can be shaped by environmental/social factors, including family and peers, which had a significant correlation to DV perpetration in the previous studies [62,63]. The inconsistent result may be due to the misconception of DV (e.g., acts of controlling a partner due to jealousy), gender stereotypes [24,26], and lack of education of DV among youth. It is necessary to verify this hypothesis and add other variables (e.g., personality traits, social support) [10,64] to this model to increase explained variance in future research.…”
Section: Main Findings and Comparison With Literaturementioning
confidence: 95%
“…Therefore, these practices of some women created a perceptual experience that all the women working in hospitality workplaces have the desire. Thus, in line with a study conducted among university students in Ethiopia [53], transactional sex practice is considered as a risk factor for SH in hospitality workplaces. Besides, exposure to transactional sex practice and engaging in commercial sex work in this study were the reported reproductive health effects of SH.…”
Section: Discussionmentioning
confidence: 62%